Patchwork ethnography - Günel, Gökçe; Watanabe, Chika (American ethnologist, 2024)
Many ethnographers feel the pressure to suspend familial and professional ties to separate “the field” from “home” for prolonged periods. Since 2019, we have been developing the concept of “patchwork ethnography” to spotlight how ethnographers conduct fieldwork amid intersecting personal and professional responsibilities. We interrogate how researchers’ personal lives impact the process of knowledge production, showcase the innovations that have stemmed from efforts to balance multiple commitments, and advocate for writing with rather than against the disruptions that might characterize anthropological research projects. As a discipline that centers reflexivity, anthropology provides the tools to rethink not only our discipline's research practices but also those of other social sciences. Drawing on the discipline's strengths, patchwork ethnography unlocks anthropology's potential to further expand what theory means and who can be considered a theorist.